Management of Therapeutic-intensity Unfractionated Heparin: A Narrative Review on Critical Points - Gouin-Thibault, Isabelle; Mansour, Alexandre; Hardy, Michael; Guéret, Pierre; de Maistre, Emmanuel; Siguret, Virginie; Cuker, Adam; Mullier, François; Lecompte, Thomas (TH Open, 2024)
Nowadays, unfractionated heparin (UFH) use is limited to selected patient groups at high risk of both bleeding and thrombosis (patients in cardiac surgery, in intensive care unit, and patients with severe renal impairment), rendering its management extremely challenging, with many unresolved questions despite decades of use.In this narrative review, we revisit the fundamental concepts of therapeutic anticoagulation with UFH and address five key points, summarizing controversies underlying the use of UFH and discussing the few recent advances in the field: (1) laboratory tests for UFH monitoring have significant limitations; (2) therapeutic ranges are not well grounded; (3) the actual influence of antithrombin levels on UFH's anticoagulant activity is not well established; (4) the concept of UFH resistance lacks supporting data; (5) scarce data are available on UFH use beyond acute venous thromboembolism.We therefore identified key issues to be appropriately addressed in future clinical research: (1) while anti-Xa assays are often considered as the preferred option, we call for a vigorous action to improve understanding of the differences between types of anti-Xa assays and to solve the issue of the usefulness of added dextran; (2) therapeutic ranges for UFH, which were defined decades ago using reagents no longer available, have not been properly validated and need to be confirmed or reestablished; (3) UFH dose adjustment nomograms require full validation.
Keywords: heparin; aPTT; anti-Xa; antithrombin; nomogram; drug resistance